2003
DOI: 10.1046/j.1525-142x.2003.03019.x
|View full text |Cite
|
Sign up to set email alerts
|

Early differentiation and migration of cranial neural crest in the opossum, Monodelphis domestica

Abstract: Marsupial mammals are born at a highly altricial state. Nonetheless, the neonate must be capable of considerable functional independence. Comparative studies have shown that in marsupials the morphogenesis of many structures critical to independent function are advanced relative to overall development. Many skeletal and muscular elements in the facial region show particular heterochrony. Because neural crest cells are crucial to forming and patterning much of the face, this study investigates whether the timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 50 publications
2
76
0
1
Order By: Relevance
“…In particular, it has been observed that, in marsupials, the tongue and oral apparatus are quite advanced, that there is a massive chondrocranium, but limited cranial ossification, that the secondary palate appears to close relatively early, that differences in the rate and pattern of dental development exist, that the jaw joint undergoes a "recapitulatory" transformation postnatally, and that the brain is relatively underdeveloped at birth. Smith and colleagues in a series of studies have examined craniofacial development in marsupials (Clark and Smith, 1993;Smith, 1994Smith, , 1996Smith, , 1997Smith, , 2001aSmith, ,b, 2002Smith, , 2003Nunn and Smith, 1998;Vaglia and Smith, 2003;van Nievelt and Smith, 2005a,b). This work has alternated between detailed model-system approaches using Monodelphis domestica as a case study, usually in comparison with the well studied murid rodents, with broader phylogenetic surveys.…”
Section: Organogenesis In the Marsupial Craniofacial Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been observed that, in marsupials, the tongue and oral apparatus are quite advanced, that there is a massive chondrocranium, but limited cranial ossification, that the secondary palate appears to close relatively early, that differences in the rate and pattern of dental development exist, that the jaw joint undergoes a "recapitulatory" transformation postnatally, and that the brain is relatively underdeveloped at birth. Smith and colleagues in a series of studies have examined craniofacial development in marsupials (Clark and Smith, 1993;Smith, 1994Smith, , 1996Smith, , 1997Smith, , 2001aSmith, ,b, 2002Smith, , 2003Nunn and Smith, 1998;Vaglia and Smith, 2003;van Nievelt and Smith, 2005a,b). This work has alternated between detailed model-system approaches using Monodelphis domestica as a case study, usually in comparison with the well studied murid rodents, with broader phylogenetic surveys.…”
Section: Organogenesis In the Marsupial Craniofacial Regionmentioning
confidence: 99%
“…In Monodelphis, neural crest cells begin to leave the neural plate at the beginning of stage 22, approximately 10 days after mating (Smith, 2001a;Vaglia and Smith, 2003) and a few hours after primitive streak formation. The stage 22 embryo consists of little more than a broad, flat neural plate.…”
Section: Differentiation and Migration Of Cranial Neural Crestmentioning
confidence: 99%
“…SEM analyses of neural crest cell migration in marsupials suggest that several timing differences exist when compared with other vertebrates (Vaglia and Smith, 2003). In particular, the onset of cranial neural crest cell migration in opossums is very early relative to neural tube and somite development when compared with mouse and chick.…”
Section: Neural Crest Cell Migration In Marsupialsmentioning
confidence: 99%
“…At this stage, which is before the initiation of somitogenesis, the neural plate is broad, flat, and open; however, preotic (presumptive r2/3 boundary) and otic (presumptive r5/6 boundary) sulci are clearly distinguishable in the neural plate. First arch neural crest cell migration commences during stage 22 in the region immediately anterior to the preotic sulcus (Vaglia and Smith, 2003). By stage 24 (six-to eight-somite stage), a substantial mass of cells has accumulated in the anterior region of the embryo as neural crest cells begin to differentiate into the broad swellings of the first (mandibular) branchial arch.…”
Section: Neural Crest Cell Migration In Marsupialsmentioning
confidence: 99%
See 1 more Smart Citation